The Impact of the Indonesian Dialect in Londo Kampung's Video on Language Attitudes: A Sociolinguistic Study - Asroriyah, Atik Muhimatun; Rohmah, Nazma Ishmaranti; Suwarni, Titi; Nabila, Zulfa (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study investigates the influence of the Indonesian dialect used in Londo Kampung’s videos on viewers’ language attitudes, highlighting the interaction between local dialects and English in digital media. The urgency of this research lies in understanding how local linguistic identities adapt and persist in English-dominated communication contexts, an issue increasingly relevant in the globalized era. Using a qualitative research design, this study analyzes linguistic features in selected videos through Howard Giles’s Communication Accommodation Theory, focusing on how vocabulary and pronunciation are tailored to diverse audiences. The analysis reveals a pattern of convergence, where speakers adjust their language to align with interlocutors, fostering mutual understanding and enhancing audience engagement. These findings contribute to sociolinguistics by demonstrating how local dialects can thrive in global contexts while influencing perceptions of identity and language attitudes. Furthermore, this study provides a foundation for future research on multilingual interactions in digital media and the preservation of local languages in the face of globalization